An intersection-movement-based stochastic dynamic user optimal route choice model for assessing network performance. (April 2015) - Long, Jiancheng; Szeto, W.Y.; Huang, Hai-Jun; Gao, Ziyou
Highlights: Use the concept of intersection movements to formulate dynamic traffic assignment. Consider stochastic dynamic user optimal principle and queue spillback. Avoid path enumeration in dynamic network loading. Show that providing better information quality may lead to more vehicle emissions. Show that enhancing link outflow capacity may lead to more emissions. Abstract: Different from traditional methods, this paper formulates the logit-based stochastic dynamic user optimal (SDUO) route choice problem as a fixed point (FP) problem in terms of intersection movement choice probabilities, which contain travelers' route information so that the realistic effects of physical queues can be captured in the formulation when a physical-queue traffic flow model is adopted, and that route enumeration and column generation heuristics can be avoided in the solution procedure when efficient path sets are used. The choice probability can be either destination specific or origin–destination specific, resulting into two formulations. To capture the effect of physical queues in these FP formulations, the link transmission model is modified for the network loading and travel time determination. The self-regulated averaging method (SRAM) was adopted to solve the FP formulations. Numerical examples were developed to illustrate the properties of the problem and the effectiveness of the solution method. The proposed models were further used to evaluate the effect of information quality and road network improvement on the network performance in terms of total system travel time (TSTT) and the cost of total vehicle emissions (CTVE). Numerical results show that providing better information quality, enhancing link outflow capacity, or constructing a new road can lead to poor network performance.